Immigration drives ship rat population irruptions in marginal high‐elevation habitat in response to pulsed resources. Issue 2 (17th February 2023) - Carpenter, Joanna K.; Monks, Adrian; Innes, John; Griffiths, James; Anderson, Dean
Abstract: Pest animal populations, such as rodents, often irrupt in response to pulsed resources. However, few studies have considered how understanding the propagation of irruptions across landscapes could lead to more efficient pest suppression. Resource pulses might create temporary source–sink dynamics in heterogeneous environments, whereby reservoirs of animals living in high‐quality habitat increase and spill over into more marginal habitat. Low‐density populations in marginal habitat could also increase through in situ breeding by residents in response to increased food availability. Understanding the relative importance of these two nonmutually exclusive processes is important as pest outbreaks could potentially be more efficiently controlled by targeting source populations early in an outbreak. We used a Bayesian hierarchical model to estimate the importance of density‐dependent emigration from lower elevation habitats versus in situ breeding by resident animals to the population growth of invasive ship rats ( Rattus rattus ) in marginal, high elevation habitats during a pulsed resource event (beech seed mast). We found that emigration from lower elevations was important for facilitating rapid population growth at high elevations, enabling rats to reach peak densities of 10.6 rats ha −1 . Without immigration, rats were predicted to reach peak densities of only 1.8 rats ha −1 at high elevation, given their densities in that habitat when we started monitoring (0.6 rats ha −1 ). This result suggests that rat control that targets low and mid‐elevations only may be sufficient to suppress irruptions in high‐elevation habitat if control effectively prevents immigration. Our study suggests spillover from higher quality habitats may enable outbreaks to rapidly propagate over landscapes. However, for r ‐selected taxa such as rodents, even very low densities of animals living in marginal habitats can increase significantly when resource pulses occur, albeit at lower densities than for populations in higher quality habitat.